Preparing Reflective Practitioners : Curriculum and Pedagogic Implications - Ramchand, Mythili (Voices of Teachers and Teacher Educators, 2018)
This paper briefly outlines what reflective practice is and why is it important for a teacher. The primary focus of the paper is on considering how reflective practice can be implemented in the teaching profession. This is dealt in three sections. The first two sections give an overview of the conceptions of reflective practice, who is considered a reflective practitioner and what constitutes reflective practice in teacher education, culled out from literature. The last section draws from these discussions to outline an approach to prepare reflective practitioners.